Sensitive electrochemical detection of p-nitrophenol by pre-activated glassy carbon electrode integrated with silica nanochannel array film - Su, Ruobing; Tang, Hongliang; Xi, Fengna (Frontiers in Chemistry, 2022)
Convenient, rapid and sensitive detection of p-nitrophenol (p-NP), one of the priority environmental pollutants, in environmental samples is of great significance. Electrochemical sensor with simple fabrication process, high sensitivity and selectivity, good antifouling, and regeneration performance is highly desirable. Herein, an electrochemical sensing platform is demonstrated based on the integration of vertically-ordered mesoporous silica-nanochannel film (VMSF) on electrochemical pre-activated glassy carbon electrode (p-GCE), which is able to realize ultrasensitive detection of p-NP in environmental samples. Electrochemical pre-activation of GCE is achieved through a simple and green electrochemical polarization process including anodic oxidation at high voltage and the following cathodic reduction at low voltage. The p-GCE possesses enhanced active area and introduced active sites, and enables stable binding of VMSF. VMSF is easily grown on p-GCE through the electrochemically assisted self-assembly (EASA) method within 10 seconds. Owing to the hydrogen bonding between silanol groups and p-NP, VMSF nanochannels display strong enrichment effect for the detection of p-NP. The developed VMSF/p-GCE sensor can achieve sensitive detection of p-NP ranging from 10 nM to 1 μM and from 1 μM to 30 μM with a limit of detection (LOD) of 9.4 nM. Considering the antifouling ability of VMSF, detection of p-NP in pond water is achieved.